Detection of Postoperative Cognitive Dysfunction by Telemedicine Among Octogenarian Patients Who Underwent Minor Elective Surgery, Prospective Cohort Study - Hathaichanok Suesat (2022)
Objective: Postoperative cognitive dysfunction (POCD) is associated with permanent disability, increased mortality, and diminished quality of life. The incidence of acute POCD among geriatric patients who have undergone minor surgery is uncertain because they are typically discharged before acute POCD is detected. Owing to the efficient postoperative care that can be provided, telemedicine is an attractive tool to investigate POCD. The primary objective of our research was to explore the incidence of acute POCD, while its secondary objective was to describe the consequences of POCD on functional recovery and quality of life. Materials and Methods: This prospective cohort study enrolled patients aged ≥ 80 years and scheduled for minor elective surgery. During pre-anesthetic visits, we installed a telecommunications program on the patients’ smartphones. Assessments of cognitive and other functions were performed preoperatively and 1 week postoperatively via telemedicine. Results: Forty octogenarian patients undergoing minor surgery were included in the final analysis. The acute- POCD incidence was 10% (95% CI 4.79-18.39). Recall memory was the main cognitive domain impaired after the procedures. Nevertheless, there were no significant differences in the functional recovery and quality of life of the POCD and non-POCD patients. Conclusion: The acute-POCD patients demonstrated minor symptoms that were unrelated to delayed postoperative functional recovery or decreased quality of life.